2017
DOI: 10.1186/s12889-017-4194-y
|View full text |Cite
|
Sign up to set email alerts
|

The EVIDENT diet quality index is associated with cardiovascular risk and arterial stiffness in adults

Abstract: BackgroundWe aimed to simplify information from food frequency questionnaires (FFQs) in a single parameter that allows for rapid identification of quality of patient diet and its relationship to cardiovascular risk and pulse wave velocity (PWV).MethodsThe sample from the EVIDENT study, consisting of 1553 subjects (aged 20–80 years) with no cardiovascular disease selected by random sampling among those attending primary care clinics, was used. The EVIDENT diet index (range 0–100) was calculated based on the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(45 citation statements)
references
References 28 publications
1
43
1
Order By: Relevance
“…We did not find any relationship between adherence to MedDiet and AS in our prepubescent MHO population. This finding is in contrast to previous studies, which show a negative correlation between AS and a healthy lifestyle based on MedDiet and physical activity in both adults [ 44 , 45 , 46 ] and children [ 4 ]. Furthermore, a lifestyle modification program in obese youth may improve AS along with reducing HOMA-IR [ 47 ].…”
Section: Discussioncontrasting
confidence: 99%
“…We did not find any relationship between adherence to MedDiet and AS in our prepubescent MHO population. This finding is in contrast to previous studies, which show a negative correlation between AS and a healthy lifestyle based on MedDiet and physical activity in both adults [ 44 , 45 , 46 ] and children [ 4 ]. Furthermore, a lifestyle modification program in obese youth may improve AS along with reducing HOMA-IR [ 47 ].…”
Section: Discussioncontrasting
confidence: 99%
“…For 7 indices, meal pattern (eg, consumption of breakfast yes or no) was included as 1 of the components 47 , 70 , 74 , 79 , 85 , 99 , 114 . Eight 43 , 48 , 51 , 59 , 100 , 101 , 108 , 110 diet quality scores separately calculate a healthy (adequacy) and unhealthy (limiting) part, such as the score from Anderson et al 59 The number and type of components included and the level of aggregation differed broadly for the listed indices, mainly depending on the target group, the intended association between the index and specific health outcome(s), and the detail of food intake data available (depending on the detail of the questionnaire used). Indices including nutrients are generally based on extensive dietary intake data collection and need valid food composition tables, which are often of limited availability in LMICs.…”
Section: Resultsmentioning
confidence: 99%
“…This correlation, although weak, remained significant after adjusting for age, sex, ethnicity, BMI, quartiles of daily kilocalories intake, and quartile of PAQ-C score. Even if to our knowledge there is no study that directly correlates fast-food intake and PWV, it has already been reported that PWV is inversely associated to healthy lifestyle and Mediterranean Diet [46,47]. “The Cardiovascular Risk in Young Finns Study” collected lifestyle data from childhood and had a 27-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In the EVIDENT cohort study, a higher adherence to the Mediterranean diet—expressed as EVIDENT, a diet index derived from the FFQ—was associated to lower values of PWV [47]. In another sample including 77 12-year-old children, adherence to the Mediterranean diet was estimated by the KIDMED index and had negative results that correlated with the Augmentation Index, independent of obesity [48].…”
Section: Discussionmentioning
confidence: 99%